Insurance Fraud Crime - Monika NIEDZWIECKA (Communications of International Proceedings, 2022)
This work presents a brief description of insurance crime. The paper presents issues concerning the definition of insurance crime, the state of insurance crime in Poland ,and possible criminal events occurring in the insurance market. In addition, activities aimed at the prevention of insurance crimes were presented, with particular emphasis on economic and legal measures.
Keywords: Insurance; Crime; Insurance Fraud.